Heterogeneity and cross-country spillovers in macroeconomic-financial linkages - Matteo Ciccarelli; Eva Ortega; Maria Teresa Valderrama (European Central Bank (ECB), 2012)
We investigate heterogeneity and spillovers in macro-financial linkages across developed economies, with a particular emphasis in the most recent recession. A panel Bayesian VAR model including real and financial variables identifies a statistically significant common component, which turns out to be very significant during the most recent recession. Nevertheless, countryspecific factors remain important, which explains the heterogeneous behaviour across countries observed over time. Moreover, spillovers across countries and between real and financial variables are found to matter: A shock to a variable in a given country affects all other countries, and the transmission seems to be faster and deeper between financial variables than between real variables. Finally, shocks spill over in a heterogeneous way across countries.
Keywords: C11; C33; E32; F44; 330; financial crisis; macro-financial linkages; panel VAR models